2007
DOI: 10.1111/j.1365-2133.2006.07655.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory or scavenging action of ketoconazole and ciclopiroxolamine against reactive oxygen species released by primed inflammatory cells

Abstract: The mechanism of the inhibitory action of KCZ against PMA-stimulated ROS production is distinct from that of CPO. Knowledge of the inhibitory or scavenging effects of both antifungal agents on ROS released from inflammatory cells may be useful in developing a therapeutic strategy for dermatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Similar results that KCZ inhibits ROS released by primed inflammatory cells (Nakashima et al, 2007) and TNFa-induced CCL27, CCL12, and CCL5 production in NHEKs (Kanda and Watanabe, 2006) have been reported; however, the underlying molecular mechanism remains unknown. The present study has identified that AhR and Nrf2, but not AhRR, are critical in the anti-inflammatory effect of KCZ in NHEKs.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Similar results that KCZ inhibits ROS released by primed inflammatory cells (Nakashima et al, 2007) and TNFa-induced CCL27, CCL12, and CCL5 production in NHEKs (Kanda and Watanabe, 2006) have been reported; however, the underlying molecular mechanism remains unknown. The present study has identified that AhR and Nrf2, but not AhRR, are critical in the anti-inflammatory effect of KCZ in NHEKs.…”
Section: Discussionsupporting
confidence: 68%
“…The mechanism by which KCZ inhibits skin inflammation has largely depended on its suppression of Malassezia spp, which contributes to the aggravation of seborrheric dermatitis (Gupta et al, 2004) and atopic dermatitis (Darabi et al, 2009). However, KCZ also exerts a direct anti-inflammatory effect (Kanda and Watanabe, 2006;Nakashima et al, 2007), the mechanism of which has remained largely unknown.…”
Section: Introductionmentioning
confidence: 98%
“…Reactive oxygen species (ROS) released from inflammatory cells constitutes one of the critical causative factors in inflammatory skin diseases such as atopic dermatitis (14). Several types of inflammatory cells such as neutrophils and macrophages play an important role in acute inflammatory processes.…”
Section: Introductionmentioning
confidence: 99%
“…However, in chronic and overaggressive inflammatory conditions, ROS may also be released into the extracellular compartment, and may cause local propagation of the inflammatory reaction and tissue damage (15,16). Therefore, the inhibition of ROS production or scavenging the released ROS may be important in preventing excess tissue damage in atopic dermatitis (14). …”
Section: Introductionmentioning
confidence: 99%
“…Antioxidative activity was estimated by the DPPH (1,1-diphenyl-2-picrylhydrazyl)-scavenging method, as described previously. 16) As for hemolytic activity, rabbit erythrocytes were obtained from Nippon Bio-Test Laboratories (Tokyo) and used within 7 d, as described previously. 17) The results of the phylogenetic analysis of the Aspergillus species preserved at NITE based on the ITS-D1/D2 region are shown in Fig.…”
mentioning
confidence: 99%